Legal Protection of the Rights of Outsourced Workers in Termination of Employment Relations - Sumba, Bacharudin Aris Setiawan; Lahaling, Hijrah; Arti, Asdar (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2023)
Legal protection for workers is very important Ensuring employee welfare, especially legal protection for outsourced employees. This happens because outsourcing practices still have no legal protection for outsourced workers. Arrangements regarding outsourcing are contained in Law no. 6 of 2023 regarding the replacement for the Job Creation Law which becomes the legal umbrella for companies and workers in terms of rights and obligations. However, in reality many things are detrimental, especially regarding the rights of workers. The rights of workers such as wages that are below the minimum, BPJS are not given. The purpose of this research was to find out the legal protection for the rights of outsourced workers in termination of employment. This study used an empirical approach. Data collection techniques included interviews with respondents and direct observation to the research location of the Gorontalo City Manpower Office, where primary data was collected, then the data analyzed descriptively. Based on the results of the research that, legal protection and rights for agency workers who work were not in accordance with the applicable rules according to Law Number 6 of 2023 concerning Job Creation